Estimating the prevalence of high-risk behaviors using network scale-up method in medical university students - Fatemeh Moghaddam Tabrizi; Rahim Sharafkhani; Zeynab Heydari; Abdolah Khorami Markani; Najaf Ahmadi Aghziyarat; Hamid Reza Khalkhali (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: There is not much information about high-risk behaviors in young groups, especially students. This study was conducted to estimate the prevalence of high-risk behaviors in students of universities of medical sciences in West Azerbaijan Province, Iran, by network scale-up (NSU) method. MATERIALS AND METHODS: This cross-sectional study was performed on 450 students from the universities of medical sciences. A researcher-developed checklist was used to collect the data. We considered number 16 for the social network size of students according to a previous study. Based on the response of individuals to each of the high-risk behaviors (including cigarette smoking, hookah use, opium consumption, alcohol drinking, tramadol/ecstasy taking, and extramarital sex) in their social network, the prevalence of these behaviors was estimated. The required calculations were performed using the NSU method. Furthermore, 95% uncertainty interval (UI) was calculated using the bootstrap method. RESULTS: Totally, 196 (44%) participants were male. The mean age (standard deviation) of the participants was 22 ± 2 years. Results showed that hookah use (20% 95% UI [18.9-21.1]) and opium consumption (0.4% 95% UI [0.24-0.6]) had the highest and lowest frequencies, respectively. Cigarette smoking (17% 95% UI [15.8-18]), alcohol use (8.3% 95% UI [7.5-9.1]), extramarital sex (8.2% 95% UI [7.4-9]), and tramadol/ecstasy taking (4% 95% UI [6.4-4.6]) were the next most common high-risk behaviors, respectively. CONCLUSIONS: Given that hookah use and cigarette smoking are the most common high-risk behaviors in students, especially males, appropriate cultural activities and educational programs should be employed by relevant authorities to reduce these behaviors.